(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2026)
The rapid growth of cloud computing, artificial intelligence, and energy-efficient computing has increased interest in alternative processor architectures beyond traditional x86 systems. This study aims to compare the characteristics, performance, and energy efficiency of x86, ARM, and RISC-V architectures through a Systematic Literature Review (SLR). Literature was collected from IEEE Xplore, ACM Digital Library, SpringerLink, arXiv, and Google Scholar covering publications from 2021 to 2026. After applying inclusion and exclusion criteria, 20 articles were selected for detailed analysis. The findings indicate that ARM and RISC-V generally provide better performance-per-watt efficiency than x86, particularly in cloud and AI-related workloads. ARM has achieved significant adoption in hyperscale cloud infrastructures due to its lower power consumption and operational costs. Meanwhile, RISC-V demonstrates strong potential through its open-source, royalty-free, and modular architecture, supported by successful hardware implementations on FPGA platforms. However, x86 continues to maintain advantages in software compatibility and ecosystem maturity. In conclusion, no single architecture is universally superior; the choice depends on application requirements, energy constraints, and software ecosystem considerations. These findings provide a comprehensive overview of current processor architecture trends and their implications for future computing systems.